Analisis Gizi Remaja Systematic Literature Review - Aditya Suhartika Suharja; Devi Kurniati; Novi Sugiharti; Rini Kundaryanti; Lisa Trina Arlym (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the nutritional status of adolescent girls using a Systematic Literature Review (SLR) approach. The study focuses on the prevalence of anemia, chronic energy deficiency (CED), and overweight in adolescents aged 12–18 years. Eight articles from the ProQuest, PubMed, SpringerLink, and ScienceDirect databases published between 2020 and 2025 and meeting PICOS criteria were analyzed using PRISMA guidelines and CEBM quality assessment. The results indicate that nutrition education, iron supplementation, technology-based interventions, and peer support have a positive impact on adolescent nutritional status. This review recommends the integration of educational interventions and school programs to improve nutritional literacy and reduce the prevalence of anemia and obesity in adolescent girls.